Early Childhood Neglect, Toxic Stress, and Neurodevelopment - Ignasi De-Bofarull; Anna Carballo-Marquez; Maria Rosa Buxarrais (Educationis Momentum, 2019)
Several and recent neuroscientific studies have accumulated empirical evidence about the maturation and neurodevelopmental processes that occur in the human brain during the first months and years of life. This immaturity gives the human brain under construction greater plasticity and learning capacity, but also leads to greater vulnerability to harmful and toxic agents from the environment. Therefore, it is considered that the care quality received in early childhood and child abuse in the form of emotional neglect, directly influence the architecture and functionality of the developing brain, both of which would elicit physiological responses of chronic and sustained (toxic) stress, being a key risk factor for the development of both physical and mental illness (anxiety and depression) in adolescence and adulthood. In this sense, a prevention model is proposed in which the first caregivers (family and school) act appropriately contributing to improve school success.